Organizational behavior - Black, Stewart; Gardner, Donald G.; Pierce, Jon L. (Jon Lepley); Steers, Richard M.; OpenStax College; BC Open Textbook Project; BCcampus (OpenStax, Rice University, 2019)
"This OpenStax resource aligns to introductory courses in Organizational Behavior. The text presents the theory, concepts, and applications with particular emphasis on the impact that individuals and groups can have on organizational performance and culture. An array of recurring features engages students in entrepreneurial thinking, managing change, using tools/technology, and responsible management; furthermore, the unique chapter on Social Media and Communication contextualizes the importance and implications of various platforms and communications methods"--BCcampus website.
Management and Organizational Behavior -- Individual and Cultural Differences -- Perception and Job Attitudes -- Learning and Reinforcement -- Diversity in Organizations -- Perception and Managerial Decision Making -- Work Motivation for Performance -- Performance Appraisal and Rewards -- Group and Intergroup Relations -- Understanding and Managing Work Teams -- Communication -- Leadership -- Organizational Power and Politics -- Conflict and Negotiations -- External and Internal Organizational Environments and Corporate Culture -- Organizational Structure and Change -- Human Resource Management -- Stress and Well Being -- Entrepreneurship -- Scientific Method in Organizational Research -- Scoring Keys for Self-Assessment Exercises.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references (pages 657-688) and index.
PDF, OB-2019-000(05/19)-RS (viewed 08 July 2019).
Keywords: Organizational behavior -- Textbooks; Corporate culture -- Textbooks; Communication in management -- Textbooks; Intercultural communication -- Textbooks; Personnel management -- Textbooks; Electronic books